’Det’ – som formelt subjekt, objekt og prædikativ i dansk - Szubert, Andrzej (Folia Scandinavica Posnaniensia, 2009)
The aim of the article is to present and analyse the usage of the lexeme det, which is one of the most frequent lexemes in Danish. Depending on the context, the lexeme in question can represent different word-classes and can among others appear as a personal or demonstrative pronoun or as a definite article. Det can also have several syntactic functions, as it can occur in Danish as a sentence’s formal subject, object or predicative. The author of the article seeks to describe this “little” word’s different functions and meanings as well as its usage in various syntactic constructions. The article also contains some reflections on the differences and similarities between det and der, in some cases a quite similar Danish lexeme.